Frontenac Mortgage Investment Corporation Announces Expected Delay in Filing Annual Financial Statements (Canada NewsWire, 2025)
Forward-Looking Statements This press release contains certain forward-looking statements and forward-looking information (collectively referred to herein as "forward-looking statements") within the meaning of applicable Canadian securities laws, which may include, but are not limited to, information and statements regarding or inferring the future business, operations, financial performance, prospects, and other plans, intentions, expectations, estimates, and beliefs of the Company, and specifically includes statements relating to the timing of the filing of the Required Documents, the redemption of shares in accordance with its Pro Rata Redemption Plan and the issuance of an MCTO. Forward-looking statements involve and are subject to assumptions and known and unknown risks, uncertainties, and other factors beyond FMIC's ability to predict or control which may cause actual events, results, performance, or achievements of FMIC to be materially different from future events, results, performance, and achievements expressed or implied by forward-looking statements herein. [...]readers are advised to rely on their own evaluation of the risks and uncertainties inherent in forward-looking statements herein and should not place undue reliance upon such forward-looking statements.